The Influence of Holistic Education Strategy on Santri’s Morally Excellent Character: The Mediating Role of Spiritual Discipline - Firdausi, Kunti Mardiyatal; Khabibah, Khilda Fitrotul; Susilawati, Samsul; Esha, Muhammad In'am (Abjadia : International Journal of Education, 2025)
This study aims to investigate the influence of holistic education strategies on santri's morally excellent character, with spiritual discipline as a mediating variable. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0 software”, data were collected from 137 santri selected through Slovin's formula from a population of 208. The results show that holistic education strategies significantly influence both spiritual discipline and morally excellent character. Furthermore, spiritual discipline plays a significant partial mediating role in the relationship between holistic education strategies and moral character. These findings highlight the importance of integrative, spiritually grounded education in shaping moral excellence among pesantren students.